Christology From Below: Methodological Issues, Global Trends, and Contextual Proposals - Shirik, Sochanngam (Transformation, 2020)
Christians, from Jerusalem to Jakarta and from the 1st to the 21st century, worship the same Jesus. However, the way that Jesus has been depicted throughout history and throughout different cultures has not been monolithic. The reason for discontinuity can be varied. One reason beneath the different descriptions of Jesus inhabits the issue of methodology. By "methodology," I mean the ways people make sense of Jesus and present him to others. Generally, there are two main approaches to the study of Christology: "from below" and "from above". This article explores the concept of Christology "from below," examining its historical development, assessing its theological assumptions, and investigating its contextual applications in the global context to cultivate some biblical principles for ongoing contextual theological conversations.